Ecotourism Around Ramsar-Listed Jagadishpur Reservoir, Lumbini Province, Nepal: Balancing Economic Growth and Environmental Sustainability - Poudel, Samichhya; Chapagain, Aashish; Puri, Puja; Pokhrel, Samiksha; Awasti, Mahesh Prasad; Bohara, Rupesh; Mahat, Anjal; Pant, Ramesh Raj (Himalayan Biodiversity, 2025)
Wetlands make up 5% of Nepal. Wetlands, both natural and man-made, are prevalent in Nepal. The largest artificial lake and most significant wetland among them is Jagadishpur, which is located in the Kapilvastu district. In developing nations, ecotourism is a rapidly growing sector that presents chances for both economic growth and the preservation of natural resources. Ecotourism has been promoted as a sustainable travel option in Nepal, which promotes community development and environmental conservation. Despite its potential, issues such as inadequate infrastructure and an absence of studies on tourist perceptions still exist. This study assesses the ecotourism potential of the Jagadishpur Reservoir in Nepal, recognizing its importance as a site of both ecological and cultural value. Data was gathered through surveys, focus group discussions, interviews, and field observations. The findings indicate that although infrastructure and marketing need to be improved, locals are aware of the potential for ecotourism. Popular attractions include bird watching, boating, and local cultural activities; however, major issues, including managing waste and insufficient promotion, hamper growth. To boost local economic development and preserve the environment, the study suggests solutions for sustainable tourist development, such as better marketing, waste management, and infrastructure. The results encourage community involvement in conservation efforts, support sustainable management techniques, and promote ecotourism policy.